2020
DOI: 10.1002/anie.202005449
|View full text |Cite
|
Sign up to set email alerts
|

Studying Natural Buckyballs and Buckybowls in Fossil Materials

Abstract: Buckyballs (fullerenes) were first reported over 30 years ago, but still little is known regarding their natural occurrence, since they have so far only been found at sites of high‐energy incidents, such as lightning strikes or meteor impacts, but have not been reported in low‐energy materials like fossil fuels. Using ultrahigh‐resolution mass spectrometry, a wide range of fullerenes from C30 to C114 was detected in the asphaltene fraction of a heavy crude oil, together with their building blocks of C10nH10 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In contrast, asphaltenes, which consist of ∼42 wt % of the entire sample, reveal a complementary compositional range to maltenes: with a similar carbon number range but a high relative abundance of species with DBE > 15 that are clustered close to the polycyclic aromatic hydrocarbon (PAH) limit. This compositional boundary (PAH limit) represents the highest possible DBE value, at a given carbon number, for planar/near planar petroleum molecules. DBE values above this limit contain nonplanar aromatic cores (fullerene-like compounds) that are most likely absent in naturally occurring petroleum. , The analyzed asphaltenes required an accumulation period ∼40-fold longer than for maltenes (200 ms, MIY ≈ 5 ms –1 ); therefore, the characterization of the entire sample preferentially reveals maltenic compounds (despite containing ∼42 wt % asphaltenes), because asphaltenes are more difficult to ionize by APPI.…”
Section: A Comprehensive Analytical Approach To Understand Ultracompl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, asphaltenes, which consist of ∼42 wt % of the entire sample, reveal a complementary compositional range to maltenes: with a similar carbon number range but a high relative abundance of species with DBE > 15 that are clustered close to the polycyclic aromatic hydrocarbon (PAH) limit. This compositional boundary (PAH limit) represents the highest possible DBE value, at a given carbon number, for planar/near planar petroleum molecules. DBE values above this limit contain nonplanar aromatic cores (fullerene-like compounds) that are most likely absent in naturally occurring petroleum. , The analyzed asphaltenes required an accumulation period ∼40-fold longer than for maltenes (200 ms, MIY ≈ 5 ms –1 ); therefore, the characterization of the entire sample preferentially reveals maltenic compounds (despite containing ∼42 wt % asphaltenes), because asphaltenes are more difficult to ionize by APPI.…”
Section: A Comprehensive Analytical Approach To Understand Ultracompl...mentioning
confidence: 99%
“…168−170 DBE values above this limit contain nonplanar aromatic cores (fullerene-like compounds) that are most likely absent in naturally occurring petroleum. 171,172 The analyzed asphaltenes required an accumulation period ∼40-fold longer than for maltenes (200 ms, MIY ≈ 5 ms −1 ); therefore, the characterization of the entire sample preferentially reveals maltenic compounds (despite containing ∼42 wt % asphaltenes), because asphaltenes are more difficult to ionize by APPI.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The study of the chemical transformation of such complex mixtures with often more than one million different chemical compounds present needs special analytical tools. Here, ultra-high-resolution mass spectrometry allows the analysis of the molecular changes of complex mixtures and as a very accurate analytical technique allows the calculation of elemental compositions from each detected signal. For these studies, a research-type Orbitrap Elite was used that allows detailed and accurate coverage of complex samples and provides elemental compositions for a large number of signals …”
mentioning
confidence: 99%
“…One observation from the results is that the maximum DBE range here is below DBE 40. While we could show that it is possible to detect hydrocarbon type compounds up to DBE 100 34 and even after a fouling reaction it was shown that nitrogen compounds up to DBE 50 can be detected, 40 here the DBE of sulfur compounds remains comparably low. However, the ionization and the reactivity of the sulfurcontaining compounds depend on their structure.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…Among them, gas chromatography/mass spectrometry (GC/MS) has been used to determine elemental sulfur in naphtha and gasoline, gel permeation chromatography (GPC) and ultrahigh resolution mass spectrometry have been successfully applied in the characterization of aromatic hydrocarbons and sulfur heterocycles in a heavy crude oil, while recently the analysis of three classes of sulfur compounds has been shown by using LC separation and an online detection and quantification by ICP-MS . High-resolution mass spectrometry (HRMS) is the method of choice for the investigation of complex mixtures due to its ability to provide high resolving power and highly accurate mass measurements. Electrospray ionization (ESI) is not commonly selected for the ionization of polycyclic aromatic sulfur hydrocarbons (PASHs) since these species are typically not basic enough to be easily protonated and this method is often used for acidic types of compounds. Thus, atmospheric pressure photoionization (APPI) is preferably used for their ionization. However, using chemical methods such as alkylation, we can achieve a selectivity toward sulfur-containing species, producing preformed ions and thus making their characterization by ESI possible .…”
Section: Introductionmentioning
confidence: 99%